The development of DNA vaccines against SARS-CoV-2 - Kanwal, Khalid *; Poh, Chit Laa * (Elsevier, 2023)
Background The COVID-19 pandemic exerted significant impacts on public health and global economy. Research efforts to develop vaccines at warp speed against SARS-CoV-2 led to novel mRNA, viral vectored, and inactivated vaccines being administered. The current COVID-19 vaccines incorporate the full S protein of the SARS-CoV-2 Wuhan strain but rapidly emerging variants of concern (VOCs) have led to significant reductions in protective efficacies. There is an urgent need to develop next-generation vaccines which could effectively prevent COVID-19.